Crushing Behaviour of Woven Roving Glass Fibre/Epoxy Laminated Composite Rectangular Tubes Subjected to 'Quasi-Static Compressive Load - Abu Khadra, Fayiz Y. M. (2002)
The automotive industry is exploring to adapting more fibre reinforced composite materials due to their stiffness to weight ratio. The amount of energy that a vehicle absorbs during a collision is a matter of concern to ensure safer and more reliable vehicle. The efficient use of composite material in the field of crash worthiness depends on the understanding of how a composite member absorbs and dissipates energy during the event of an impact. An experimental and finite element investigation of the woven roving glass fibre/epoxy laminated composite rectangular tubes subjected to compressive loading were carried out under compressive loading. Through out this investigation, rectangular tubes with different cross-sectional aspect ratio varying (alb) from 1 to 2 with 0.25 increment were investigated under axial and lateral loading conditions applied independently. The effects of increasing the cross-sectional aspect ratio on the load carrying capacity and the energy absorption capability were also presented and discussed. Finite element models to predict the load carrying capacity, failure mechanism and stress contours at pre-crush stage of the rectangular tubes under axial and lateral loading conditions have been developed. Experimental results show that the cross-sectional aspect ratio significantly affects the load carrying capacity and the energy absorption capability of the tubes. The axially loaded rectangular tubes have better load carrying capacity and energy absorption capability compared to the laterally loaded rectangular tubes. The buckling failure mode has been identified for the rectangular tubes under the different loading conditions. The developed finite element models approximately predict the initial failure load and the deformed shapes. The discrepancy between the finite element prediction and the experimental results is due to the assumption made in the finite element models and not considering the imperfection of the real tubes in the finite element models. From the experimental and finite element results 'knockdown' factors have been proposed to be used in the design phase of energy absorption elements to predict the initial failure load.